ENHANCING EMPLOYEE WELL-BEING IN THE DIGITAL BUSINESS LANDSCAPE: EXPLORING THE NEXUS OF WORK-LIFE HARMONYAND ORGANIZATIONAL SUPPORT - Januar Ida Wibowati; Yuli Alam; Ahmad Rizani; Loso Judijanto; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
The consistently developing computerized business scene presents particular difficulties to the prosperity of workers. This study dives into the complicated connection between work-life amicability, hierarchical help, and representative prosperity in this unique setting. The examination utilizes a blended technique approach, joining quantitative studies and subjective meetings to acquire an extensive comprehension. The outcomes demonstrate that representatives in the computerized business world see a respectably certain work-life congruity, and they report an elevated degree of hierarchical help. Critically, a positive connection between work-life concordance and representative prosperity is noticed, featuring the meaning of accomplishing a decent expert and individual life. Furthermore, the study underscores the pivotal role of organizational support mechanisms, such as mental health resources and flexible work arrangements, in enhancing employee well-being. The implications of this study are twofold. First, it offers practical guidance for digital businesses to prioritize work-life harmony and strengthen organizational support to foster employee well-being. Second, it highlights the universal importance of these factors in the digital business context, reaffirming their relevance in an ever-changing landscape. Future research directions include longitudinal studies and a more in-depth exploration of industry-specific nuances. This study's overall significance lies in its role as a compass, guiding organizations toward a future where employee well-being and business success are intricately intertwined.